(3GdehUd (B: (3aj GdYgOjf GdQGTOj hGdGehj(B/s - (3GdSdeGf,YHO GdeGLhO GMeO s ((3GdehUd , (B[(3GdYQGb(B] :s (3efThQGJ ecJHI HSGe ,s, 1985)
(3jJVef eSJNdU HGddZI GdGfcdjRjI s
(3jJVFeI bGFeI HGdeUGOQ ef UaMI (B215-264s
(3jJVef GQLGYGJ HHdjhZQGajIs
Keywords: (3GdehUds -- (3JGQjNs -- (3GdYUQ GdQGTOjs